Intervención de enfermería en adulto mayor de 65 años con diabetes mellitus tipo 2 insulino dependiente con hiperplasia prostática. - Salazar Calero, Aracelly Belén (2020)
The present case called nursing intervention in adults older than 65 years with insulin-dependent diabetes mellitus type 2 with prostatic hyperplasia. The objective was to determine the appropriate nursing intervention in a patient with these two pathologies and to analyze the patient's information through objective and subjective data that allow establishing the patient's needs and health problems. The present case obtained favorable results for both the patient and the health personnel, effectively concluding the chosen treatment, in order to have maximum benefit and use of the study, being for the scope and purpose of its preparation, waiting that it can serve as an indicator parameter and source of information and thus decrease the various complications that this disease brings, and raise awareness that unhealthy habits could lead to death being a very high priority problem in public health.